Midway [videorecording (DVD)] - Harrelson, Woody; Wilson, Patrick, 1973-; Evans, Luke, 1979- (Lionsgate, 2020)
Centers on the Battle of Midway, a clash between the American fleet and the Imperial Japanese Navy which marked a pivotal turning point in the Pacific Theater during WWII. The film, based on the real-life events of this heroic feat, tells the story of the leaders and soldiers who used their instincts, fortitude, and bravery to overcome the odds.